Management Strategy of Educational Administration through Academic Information Systems - Hasnah Hasnah; Wilrahmi Izati; Hamdani Abdi; Syamsul Kurniawan; Hamam Burhanuddin (AT-TA'LIM, 2024)
The rapid development of information and communication technology has significantly influenced the management of higher education institutions, particularly in academic administration. Higher education institutions are required to adopt effective information systems to enhance efficiency, transparency, and service quality. STAI-PIQ West Sumatra has implemented an Academic Information System (SIAKAD) as part of its educational administration management strategy. This study aims to analyze the implementation of educational administration management through an academic information system at STAI-PIQ West Sumatra. The research employed a descriptive qualitative approach, with data collected through observation, documentation, and literature review. Data were analyzed using thematic analysis to identify patterns and roles of the academic information system in educational management. The findings indicate that the implementation of SIAKAD supports integrated academic management processes, including planning, implementation, and evaluation of academic activities. The system facilitates efficient management of academic data related to students, lecturers, curriculum, scheduling, assessment, and financial administration. Furthermore, SIAKAD contributes to improved administrative efficiency, data accuracy, and managerial decision-making, thereby supporting the achievement of the institution’s vision, mission, and strategic objectives. In conclusion, the academic information system plays a crucial role in strengthening educational administration management at STAI-PIQ West Sumatra. This study recommends continuous system development, enhancement of human resource competencies, and institutional commitment to technology-based management to optimize the effectiveness of academic information systems in Islamic higher education institutions.